Preparation method of alloy product and micro-arc oxidation layer plus paint composite film
By forming a microarc oxide layer on the lightweight alloy material and applying a combination of UV transparent paint and paint oil, the problem of poor performance of the protective film layer is solved, and an efficient and environmentally friendly protective effect is achieved, which is suitable for a variety of technical fields.
Patent Information
- Application Number
- CN202310465944.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-19
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-04-19
AI Technical Summary
The protective film layer of existing lightweight alloy materials has poor protection performance, making it difficult to achieve industrial production, and the traditional paint baking process leads to increased weight, unfriendly environment, and thin profiles are prone to deformation.
Using a micro-arc oxide layer and a protective paint film composite film layer, a combination of UV transparent paint, UV color oil, curing agent, diluent and paint oil is used to form a thermally cured protective coating, which is pre-dryed, UV light irradiated and Bake to form a composite film layer.
It significantly improves the protective performance of alloy products, reduces weight increase and organic volatiles, avoids deformation caused by high-temperature baking, and meets application needs in the fields of aviation, navigation, electronic products, etc.
Smart Images

Figure CN116515351B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material protective films, in particular to a method for preparing an alloy product and a micro-arc oxidation layer plus a paint coating composite film layer. Background Art
[0002] Electronic products, military products, marine and aviation products, watch accessories, automotive products and daily tools are generally made of light alloy materials, such as magnesium alloy and aluminum alloy. However, the above materials are prone to corrosion in the environment in which they are used, so the protection of light alloy materials is a research hotspot at this stage.
[0003] The protection of lightweight alloy materials specifically includes the following methods: coating UV paint on the surface of the material to obtain a UV protective film. The preparation process of the protective film is simple, but its protective adhesion performance is poor. The 100-grid test at 80°C or above will cause bubbling, and the salt spray test will cause bubbling when the film layer is thrown on with NICHIBAN CT405AP-24 tape, or 3M series adhesive tape, etc., and the 100-grid test will fail. The reliability does not meet the requirements, and the process is difficult to achieve industrial production; or, baking paint is applied on the surface of the material by spraying 2 or more coats: 1 primer, then 1 topcoat (second coat), or 3 coats (primer, midcoat and topcoat, in sequence). The color of the protective film is stable, but the thickness of the spray paint increases, which increases the weight, produces more volatile organic compounds, is not environmentally friendly, and is prone to deformation during the baking paint process for the protection of thin profiles, and high-quality protective products cannot be obtained. Summary of the invention
[0004] Based on this, the present invention provides an alloy product, which solves the technical problem of poor protective performance of the existing alloy material protective film layer by setting a maintenance oxide layer and a protective paint film conforming to the film layer.
[0005] The first object of the present invention is to provide an alloy product, the alloy product comprising an alloy substrate and a composite film layer of a micro-arc oxidation layer and a protective paint film sequentially arranged on the surface of the alloy substrate;
[0006] The raw materials for preparing the protective paint film include the following components: UV transparent paint, UV color oil, curing agent, diluent and baking paint oil;
[0007] The UV transparent paint is an oily acrylic UV paint; the baking paint oil is an oily acrylic baking paint, and the baking paint oil includes: isobutyl acetate and / or ethyl acetate.
[0008] In some specific embodiments, the weight of the baking varnish oil is 5-30% of the sum of the weights of the UV transparent varnish and the UV color oil.
[0009] In some specific embodiments, the weight ratio of the UV transparent paint, the UV color oil, the curing agent and the diluent is: (40-60): (40-60): (4-6): (48-72).
[0010] In some specific embodiments, the curing temperature of the UV transparent paint is 70-80°C, and the curing temperature of the baking paint oil is 147-153°C.
[0011] In some specific embodiments, the UV color oil is an oily acrylic UV color oil.
[0012] In some specific embodiments, the curing agent is a diisocyanate curing agent.
[0013] In some specific embodiments, the diluent is a ketone diluent, including one or more of acetone, methyl ethyl ketone, cyclohexanone and methyl isobutyl ketone.
[0014] In some specific embodiments, the alloy matrix is a magnesium alloy, an aluminum alloy or a titanium alloy.
[0015] In some specific embodiments, the thickness of the micro-arc oxidation layer is 2 to 50 μm; and / or the thickness of the protective paint film is 2 to 50 μm.
[0016] The embodiment of the present invention also provides a method for preparing a micro-arc oxidation layer plus a paint coating composite film layer, comprising the following steps:
[0017] S1: Stir and mix UV color oil, UV transparent paint and baking paint oil, and then add curing agent and diluent and stir and mix to obtain protective coating;
[0018] S2: subjecting the surface of the alloy substrate to micro-arc oxidation treatment to form a micro-arc oxidation layer;
[0019] S3: applying the protective coating to the surface of the maintenance oxide layer, irradiating it with UV light after pre-drying, and then baking it to form a protective paint film to obtain an alloy product containing a composite film layer.
[0020] In some specific embodiments, the pre-drying temperature in the pre-drying process is 80-90° C., and the pre-drying time is 8-15 minutes.
[0021] In some specific embodiments, the baking temperature in the baking process is 80-100° C., and the baking time is 150-240 minutes.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The above alloy product of the present invention, after the micro-arc oxidation is performed on the alloy surface to form a micro-arc oxidation layer, is coated with a protective coating composed of a combination of heat-cured baking varnish oil and UV paint, and after pre-drying, UV light treatment and baking, a composite protective film alloy product containing a micro-arc oxidation layer and a protective paint film layer is obtained. The preparation process is simple, and one coating method is used instead of two or three coatings or more. a) The weight increase of the alloy material can be reduced to the greatest extent and can be used for carrying; b) 1 to 3 layers of paint can be sprayed less, which is beneficial to reducing the thickness of the product; c) high-temperature baking greater than 100°C is not required to avoid deformation, which is beneficial to the stability of the process molding; d) organic volatiles are reduced exponentially, which is beneficial to improving environmental protection contributions; e) the cost of oil spraying is reduced; d) the overall appearance is good, market sales and excellent use effects.
[0024] The breakthrough and innovative combination of baked acrylic type baking varnish oil and acrylic type UV transparent paint can improve the hard and brittle properties of the paint film formed by UV paint, increase the toughness and tenacity of the paint film, and also improve the performance of the micro-arc oxidation layer by 10 to 50 times. The composite protective film of the alloy product obtained has good toughness, friction resistance is improved by orders of magnitude, drop resistance is improved by orders of magnitude, and corrosion resistance is improved by orders of magnitude, which meets the application of lightweight materials in technical fields such as aviation, navigation, electronic products, golf, and automobiles. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a physical picture of the magnesium alloy composite film product obtained in Example 1 after the water boiling test;
[0026] Figure 2 This is a physical picture of the magnesium alloy composite film product obtained in Example 1 after the neutral salt spray test;
[0027] Figure 3 The actual picture of the magnesium alloy composite film product obtained in Comparative Example 1 after the water boiling hundred grid test; a) is the actual picture after the water boiling experiment, b) is the actual picture of the hundred grid test after water boiling;
[0028] Figure 4 The following are the actual pictures of the magnesium alloy composite film product obtained in Comparative Example 1 after the neutral salt spray test; a) is the actual picture after the neutral salt spray test, and b) is the actual picture of the hundred-grid test after the neutral salt spray test. DETAILED DESCRIPTION
[0029] For ease of understanding of the present invention, the present invention will be described more fully below with reference to relevant embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0030] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the invention, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present invention, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0031] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0032] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0033] Unless otherwise specified, all percentages, fractions and ratios are calculated by the total mass of the composition of the present invention. Unless otherwise specified, all masses of the listed ingredients are given to the content of active substances, so they do not include solvents or by-products that may be contained in commercially available materials. The term "mass percentage content" herein can be represented by the symbol "%". Unless otherwise specified, all molecular weights in this article are weight average molecular weights expressed in Daltons. Unless otherwise specified, all formulations and tests in this article occur in an environment of 25°C. "Including", "including", "containing", "containing", "having" or other variants herein are intended to cover non-closed inclusions, and these terms are not distinguished. The term "comprising" means that other steps and ingredients that do not affect the final result can be added. The composition and method / process of the present invention include, consist of and are essentially composed of the necessary elements and restrictions described herein and any additional or optional ingredients, components, steps or restrictions described herein. The terms "efficacy", "performance", "effect" and "efficacy" are not distinguished between herein.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0035] An embodiment of the present invention provides an alloy product, which includes an alloy substrate, a micro-arc oxidation layer and a protective paint film sequentially arranged on the surface of the alloy substrate; the raw materials for preparing the protective paint film include the following components: UV transparent paint, UV color oil, curing agent, diluent and baking paint oil; the UV paint is an acrylic UV paint, under the irradiation of ultraviolet light, the initiator decomposes, generates free radicals, triggers the resin reaction, and solidifies into a film. The baking paint oil is an acrylic baking paint containing isobutyl acetate, ethyl acetate, etc., which is a high-temperature heat-curing baking paint oil, and the curing temperature is 147-153°C.
[0036] The "one-coat protective paint film" refers to a protective paint film obtained by directly curing the paint after spraying it once. Compared with the prior art which requires spraying it 2, 3 or more times, the process is simple, the film layer is light in weight, and produces less volatile substances.
[0037] Acrylic UV paint and acrylic baking varnish are the same type of paint. Using the principle of like dissolves like, the innovative proposal and successful verification have cleverly combined the acrylic UV paint cured at low temperature of 80℃ and the acrylic baking varnish cured at high temperature of 150℃, and thoroughly cured and cross-linked at low temperature of 90℃, taking the advantages of both and removing the disadvantages to achieve excellent adhesion and reliability of the combined film layer, avoiding the deformation of the product caused by high temperature curing of high temperature baking varnish spraying, and avoiding the poor adhesion of the cured film layer of low temperature UV paint spraying.
[0038] The weight of the baking varnish oil is 5% to 30% of the sum of the weights of the UV transparent paint and the UV color oil, preferably 5% to 20%. In some embodiments, the amount of baking varnish oil added is 5%, 10%, 15%, or 20% of the sum of the weights of the UV transparent paint and the UV color oil. Further, when the amount of baking varnish oil added is 5% to 10% of the sum of the weights of the UV transparent paint and the UV color oil, the color of the protective paint film is very close to the color of the UV color oil, and when the amount of baking varnish oil added is 15% to 20% of the sum of the weights of the UV transparent paint and the UV color oil, the color of the protective paint film tends to be close to the color of the baking varnish paint.
[0039] The weight ratio of UV transparent paint, UV color oil, curing agent and diluent in the raw materials of the protective paint film is (40-60):(40-60):(4-6):(48-72), preferably 50:50:6:60.
[0040] In some specific examples, the curing agent is a diisocyanate type, specifically including isophorone diisocyanate, toluene diisocyanate, hexyl diisocyanate, hexamethylene diisocyanate, and / or contains hydroxyl and carboxyl groups. In the protective coating system, the curing agent causes irreversible changes in the thermosetting resin material to form a stable protective paint film.
[0041] In some specific examples, the UV color oil is a color dispersion carrier containing a pigment, and the carrier is an oily acrylic resin, including: unsaturated polyester acrylate and / or polyurethane acrylate, which is compatible with other ingredients, and the pigment can be selected according to actual color requirements.
[0042] In some specific examples, the diluent is a ketone type, including one or more of acetone, methyl ethyl ketone, cyclohexanone and methyl isobutyl ketone. In the protective coating system, the diluent can adjust the viscosity and fluidity of the resin material in the coating to obtain a liquid protective coating with good miscibility, which is beneficial to the leveling and uniformity of the paint film in the subsequent spray coating process.
[0043] In some specific examples, the alloy matrix is a magnesium alloy, an aluminum alloy or a titanium alloy.
[0044] In some specific examples, the thickness of the micro-arc oxidation layer is 2-20 μm. In some embodiments, the thickness of the protective paint film is 2-20 μm.
[0045] The above alloy product, after the alloy surface is subjected to micro-arc oxidation to form a black micro-arc oxidation layer, is coated with a protective coating composed of a combination of heat-cured baking varnish oil and UV paint, and after pre-drying, UV light treatment and baking, a composite protective film alloy product containing a micro-arc oxidation layer and a protective paint film layer is obtained. The preparation process is simple, and one coating method replaces two or three coatings or more, which can minimize the weight increase of the alloy material, and does not require high-temperature baking greater than 100°C to avoid deformation, and reduces organic volatiles by several times, and reduces the cost of oil spraying by several times, which is conducive to weight reduction, thinning, and products with appearance exceeding quality requirements. The combination of acrylic baking varnish oil and acrylic UV paint with breakthrough innovation can improve the hard and brittle properties of the paint film formed by UV paint, increase the toughness and toughness of the paint film, and also improve the performance of the micro-arc oxidation layer by 10 to 50 times. The composite protective film of the alloy product obtained has good toughness, friction resistance is improved by an order of magnitude, drop resistance is improved by an order of magnitude, and corrosion resistance is improved by an order of magnitude, which meets the application of lightweight materials in the technical fields of aviation, navigation, electronic products, golf, automobiles, etc.
[0046] Another embodiment of the present invention provides a method for preparing a micro-arc oxidation layer plus a paint coating composite film layer of the above alloy product, comprising the following steps:
[0047] S1: Mix UV color oil, UV transparent paint and baking paint oil in proportion, then add curing agent and diluent and mix to obtain protective coating; the protective coating generally follows the principle of preparing and using immediately, and after being evenly stirred, it needs to be sprayed and used up within 1 to 24 hours to ensure reliable and excellent film quality.
[0048] S2: subjecting the surface of the alloy substrate to micro-arc oxidation treatment to form a micro-arc oxidation layer;
[0049] S3: spray-coating the protective coating onto the surface of the micro-arc oxidation layer, irradiating it with UV light after pre-drying, and then baking it to form a protective paint film to obtain an alloy product with a composite film layer of excellent quality.
[0050] The coating includes spraying, brushing, scraping, screen coating and the like, with spraying being preferred.
[0051] In some embodiments, the pre-drying temperature in the pre-drying process is 80-90° C., and the pre-drying time is 8-15 minutes. In some embodiments, the baking temperature in the baking process is 80-100° C., and the baking time is 150-240 minutes.
[0052] In a specific example, the micro-arc oxidation includes the following technical features:
[0053] The process and specific parameters of black micro-arc oxidation, micro-arc oxidation solution: sodium silicate 8-40g / L, sodium hydroxide 3-10g / L, sodium fluoride 5-20g / L, sodium hexametaphosphate 10-40g / L, sodium metavanadate 8-40g / L. At a temperature of 15-35°C, the current density is 0.8-8A / dm 2 , frequency 800~1800HZ, duty cycle 5~30%, time 3~20 minutes, form a micro-arc oxidation layer on the surface of magnesium alloy. The thickness of the black film of micro-arc oxidation film is 5~20μm.
[0054] In the one-coat preparation process, the volatile gas partially evaporates through the pre-drying process, and the paint is leveled and initially cured, thereby ensuring the flatness and glossiness of the paint film; then, through UV light irradiation, free radical photo-initiated polymerization and cross-linking reactions are generated, and finally a long-term baking and curing is performed to form a paint film. The process is simple, with only one coating, UV light treatment and baking, mild conditions, and low baking temperature. It is suitable for products that are not resistant to high temperature deformation above 110°C, extremely lightened products, and extremely thinned products. It consumes less resources, produces less volatile gases, and is environmentally friendly.
[0055] The present invention is described in detail below by taking alloy products as an example in combination with specific embodiments. These embodiments are used for understanding rather than for limiting the present invention.
[0056] In the following examples, UV transparent paint, UV color oil, curing agent, diluent, and baking oil are all purchased from new paints developed and verified by Musashi Paint Co., Ltd. that meet the company's internal standards, as follows:
[0057] UV clear paint: acrylic UV paint, model: ULTRA VIN EC-UV 2400-S1 MATT CLEAR modified 1, matte paint, curing temperature is 75±10℃, UV energy is 80±20mW / cm 2 .
[0058] The UV color oil model is: ULTRA VIN EC-UV 24-S22-34631 UV blue.
[0059] Baking varnish oil: contains isobutyl acetate, ethyl acetate and methyl isobutyl ketone, with a curing temperature of 150±3℃. Specific models include:
[0060] The baking varnish oil I is WD33-C22-64183 ARMOR TOP transparent blue.
[0061] The paint oil II is WD33-C23-64927 matte transparent blue.
[0062] Curing agent: diisocyanate H304.
[0063] Diluent: Ketone diluent.
[0064] Diluent I is EXT-1009.
[0065] Diluent II is ARMOR TOP 2253.
[0066] It should be understood that the raw materials in the present invention can be acrylic UV paint, UV color oil and acrylic baking paint oil prepared by other companies, as long as they can meet the curing temperature and contain corresponding ingredients.
[0067] Example 1
[0068] Weigh the raw materials according to the formula of 50 parts of UV transparent paint, 50 parts of UV color oil, 5 parts of curing agent, 60 parts of diluent, and 10 parts of baking varnish oil I. After the color oil, UV transparent paint and baking varnish oil are stirred and mixed evenly, the curing agent and diluent are added and stirred to obtain a protective coating.
[0069] Take a magnesium alloy plate with a thickness of 1.5 mm and perform micro-arc oxidation on the magnesium alloy. The process and specific parameters of black micro-arc oxidation are as follows: the micro-arc oxidation solution is: sodium silicate 10g / L, sodium hydroxide 6g / L, sodium fluoride 10g / L, sodium hexametaphosphate 20g / L, sodium metavanadate 15g / L, at a temperature of 20°C and a current density of 1.8A / dm 2The micro-arc oxidation was carried out for 10 minutes at a frequency of 1800 Hz and a duty cycle of 10%, and a micro-arc oxidation layer was formed on the surface of the magnesium alloy. The obtained black film of the micro-arc oxidation film was 10±2 μm thick.
[0070] The protective paint spray coating was applied on the surface of the micro-arc oxidation layer, pre-dried at 90°C for 10 minutes, then passed through a UV machine for two times of UV light, and baked at 90°C for 180 minutes to form a protective paint film (protective paint film thickness 15±3μm) to obtain a magnesium alloy composite film product.
[0071] Example 2
[0072] Weigh the raw materials according to the formula of 50 parts of UV paint, 50 parts of color oil, 5 parts of curing agent, 60 parts of diluent, and 5 parts of baking varnish oil II. After the color oil, UV paint and baking varnish oil are stirred and mixed evenly, the curing agent and diluent are added and stirred to obtain the protective coating.
[0073] Take a magnesium alloy plate with a thickness of 1.5 mm and perform micro-arc oxidation on the magnesium alloy. The process and specific parameters of black micro-arc oxidation are as follows: the micro-arc oxidation solution is: sodium silicate 10g / L, sodium hydroxide 6g / L, sodium fluoride 10g / L, sodium hexametaphosphate 20g / L, sodium metavanadate 15g / L, at a temperature of 20°C and a current density of 1.8A / dm 2 The micro-arc oxidation was carried out for 10 minutes at a frequency of 1800 Hz and a duty cycle of 10%, and a micro-arc oxidation layer was formed on the surface of the magnesium alloy. The obtained black film of the micro-arc oxidation film was 10±2 μm thick.
[0074] The protective paint spray coating was applied on the surface of the micro-arc oxidation layer, pre-dried at 80°C for 10 minutes, then passed through a UV machine for two times of UV light, and baked at 90°C for 180 minutes to form a protective paint film (protective paint film thickness 15±3μm) to obtain a magnesium alloy composite film product.
[0075] Example 3
[0076] Weigh the raw materials according to the formula of 50 parts of UV paint, 50 parts of color oil, 5 parts of curing agent, 60 parts of diluent, and 15 parts of baking varnish oil II. After the color oil, UV paint and baking varnish oil are stirred and mixed evenly, the curing agent and diluent are added and stirred to obtain a protective coating.
[0077] Take a magnesium alloy plate with a thickness of 1.5 mm and perform micro-arc oxidation on the magnesium alloy. The process and specific parameters of black micro-arc oxidation are as follows: the micro-arc oxidation solution is: sodium silicate 10 g / L, sodium hydroxide 6 g / L, sodium fluoride 10 g / L, sodium hexametaphosphate 20 g / L, sodium metavanadate 15 g / L, at a temperature of 20 ° C and a current density of 1.8 A / dm 2The micro-arc oxidation was carried out for 10 minutes at a frequency of 1800 Hz and a duty cycle of 10%, and a micro-arc oxidation layer was formed on the surface of the magnesium alloy. The obtained black film of the micro-arc oxidation film was 10±2 μm thick.
[0078] The protective paint spray coating was applied on the surface of the micro-arc oxidation layer, pre-dried at 80°C for 10 minutes, then passed through a UV machine for two times of UV light, and baked at 90°C for 180 minutes to form a protective paint film (protective paint film thickness 15±3μm) to obtain a magnesium alloy composite film product.
[0079] Comparative Example 1
[0080] According to the formula, 50 parts of UV transparent paint, 50 parts of color oil, 5 parts of curing agent, 60 parts of diluent and 10 parts of baking varnish oil are weighed, the color oil and UV transparent paint are stirred and mixed evenly, and then the curing agent and diluent are added and stirred to obtain the protective coating.
[0081] Take a magnesium alloy plate with a thickness of 1.5 mm and perform micro-arc oxidation on the magnesium alloy. The process and specific parameters of black micro-arc oxidation are as follows: the micro-arc oxidation solution is: sodium silicate 10g / L, sodium hydroxide 6g / L, sodium fluoride 10g / L, sodium hexametaphosphate 20g / L, sodium metavanadate 15g / L, at a temperature of 20°C and a current density of 1.8A / dm 2 The micro-arc oxidation was carried out for 10 minutes at a frequency of 1800 Hz and a duty cycle of 10%, and a micro-arc oxidation layer was formed on the surface of the magnesium alloy. The obtained black film of the micro-arc oxidation film was 10±2 μm thick.
[0082] The protective coating was sprayed on the surface of the micro-arc oxidation layer, pre-dried at 90°C for 8 minutes, then passed through a UV machine for 2 times of UV light, and baked at 90°C for 180 minutes to form a protective paint film (protective paint film thickness 15±3μm) to obtain a magnesium alloy composite film product.
[0083] Comparative Example 2
[0084] The baking varnish oil II and the thinner II were stirred and mixed evenly in a ratio of 50:60 to obtain a protective coating.
[0085] Take a magnesium alloy plate with a thickness of 1.5 mm and perform micro-arc oxidation on the magnesium alloy. The process and specific parameters of black micro-arc oxidation are as follows: the micro-arc oxidation solution is: sodium silicate 10g / L, sodium hydroxide 6g / L, sodium fluoride 10g / L, sodium hexametaphosphate 20g / L, sodium metavanadate 15g / L, at a temperature of 20°C and a current density of 1.8A / dm 2 The micro-arc oxidation was carried out for 10 minutes at a frequency of 1800 Hz and a duty cycle of 10%, and a micro-arc oxidation layer was formed on the surface of the magnesium alloy. The obtained black film of the micro-arc oxidation film was 10±2 μm thick.
[0086] The protective coating was sprayed on the surface of the micro-arc oxidation layer with a spraying thickness of 13±3 μm, and baked at 150° C. for 30 minutes to form a protective paint film to obtain a magnesium alloy composite film product, which was deformed.
[0087] Comparative Example 3
[0088] The baking varnish oil I and the thinner II were stirred and mixed evenly in a ratio of 50:60 to obtain a protective coating.
[0089] Take magnesium alloy rods and perform micro-arc oxidation on the magnesium alloy. The process and specific parameters of black micro-arc oxidation are as follows: the micro-arc oxidation solution is: sodium silicate 10g / L, sodium hydroxide 6g / L, sodium fluoride 10g / L, sodium hexametaphosphate 20g / L, sodium metavanadate 15g / L, at a temperature of 20°C and a current density of 1.8A / dm 2 The micro-arc oxidation was carried out for 10 minutes at a frequency of 1800 Hz and a duty cycle of 10%, and a micro-arc oxidation layer was formed on the surface of the magnesium alloy. The obtained black film of the micro-arc oxidation film was 10±2 μm thick.
[0090] The protective coating was sprayed on the surface of the micro-arc oxidation layer with a spraying thickness of 13±3 μm, and baked at a high temperature of 150° C. for 30 minutes to form a protective paint film to obtain a magnesium alloy composite film product.
[0091] Performance Testing
[0092] The composite film on the surface of the alloy material obtained in Examples 1 to 3 and Comparative Examples 1 to 3 was subjected to a hundred-grid test: a 1mm×1mm small grid was cut using a hundred-grid knife or a surgical blade, and a NICHIBAN CT405AP-24 tape was attached. After standing for (90±30)s, one end of the tape was held in the air, and the tape was quickly pulled back within 0.5 to 1.0s at an angle as close to 60 degrees as possible. The same position was tested once, and the ASTM D3359 and ISO 2409 rating scales were used for rating. After boiling at 80°C, a 1mm×1mm hundred-grid test was performed, as well as a 72-hour salt spray (35°C±2°C, 85%RH salt spray box, 5%±1%NaCl solution was continuously sprayed for 72h, pH value 6.5 to 7.2), and then a 1mm×1mm hundred-grid test was performed. The salt spray test experiment was evaluated using the evaluation standard ASTM B537. The results obtained are shown in Table 1 and Figures 1 to 4 shown.
[0093] Table 1 Parameters and performance test results of composite film made by spraying oil on black micro-arc oxidation film layer
[0094]
[0095] according to Figures 1 to 4It can be seen that the UV transparent paint of the present invention and the baking varnish oil are combined to form a new type of protective coating, such as Figure 1 , 2 As shown, after the boiling water 100 grid test and the neutral salt spray 100 grid test, there is no blistering and corrosion, and the evaluation grade is 5B, which is qualified and suitable for products with thin and high quality requirements.
[0096] When the paint oil is omitted, Figure 3 , 4 As shown, after the water boiling 100 grid test and the neutral salt spray 100 grid test, bubbles were generated and the rating was 0B, which was unqualified.
[0097] When the composite film is formed by using baking varnish oil and micro-arc oxidation layer, there is no blistering and corrosion after relevant experiments, and the rating is 5B, which is qualified. However, for thin profiles, deformation occurs during the baking process.
[0098] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0099] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An alloy product, characterized in that: The alloy product comprises an alloy substrate and a composite film layer of a micro-arc oxidation layer and a protective paint film sequentially arranged on the surface of the alloy substrate, wherein the micro-arc oxidation layer is a black micro-arc oxidation layer; the thickness of the micro-arc oxidation layer is 10±2µm; the thickness of the protective paint film is 15±3μm; The raw materials for preparing the protective paint film are composed of UV transparent paint, UV color oil, curing agent, diluent and baking paint oil; The UV transparent paint is an oily acrylic UV paint, and the curing temperature of the UV transparent paint is 70°C to 80°C; the baking paint oil is an oily acrylic baking paint, and the baking paint oil also includes: isobutyl acetate, ethyl acetate and methyl isobutyl ketone, and the baking curing temperature is 147°C to 153°C; The UV color oil is an oily acrylic UV color oil; The curing agent is a diisocyanate curing agent; The diluent is a ketone diluent; The weight of the baking varnish oil is 5% to 15% of the sum of the weights of the UV transparent varnish and the UV color oil; The weight ratio of the UV transparent paint, the UV color oil, the curing agent and the diluent is 50:50:6:
60.
2. The alloy product according to claim 1, characterized in that: The diluent includes one or more of acetone, methyl ethyl ketone, cyclohexanone and methyl isobutyl ketone.
3. The alloy product according to claim 1, characterized in that: The alloy matrix is a magnesium alloy, an aluminum alloy or a titanium alloy.
4. The method for preparing an alloy product according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: S1: Stir and mix UV color oil, UV transparent paint and baking varnish oil, and then add curing agent and diluent and stir and mix to obtain protective coating; S2: subjecting the surface of the alloy substrate to micro-arc oxidation treatment to form a micro-arc oxidation layer; S3: applying the protective coating to the surface of the micro-arc oxidation layer, irradiating it with UV light after pre-drying, and then baking it to form a protective paint film to obtain an alloy product containing a composite film layer.
5. The method for preparing an alloy product according to claim 4, characterized in that: The pre-drying temperature in the pre-drying process is 80° C. to 90° C., and the pre-drying time is 8 minutes to 15 minutes.
6. The method for preparing an alloy product according to claim 4, characterized in that: The baking temperature in the baking process is 80° C. to 100° C., and the baking time is 150 minutes to 240 minutes.
